2014
DOI: 10.1075/sic.11.1.02oro
|View full text |Cite
|
Sign up to set email alerts
|

The future tense in Spanish L2 textbooks

Abstract: This paper revisits the treatment of the expression of futurity in Spanish foreign language (FL) textbooks. We analyzed twenty college-level Spanish FL textbooks to determine and quantify how futurity is represented. Variationist research has shown the periphrastic future (PF) to be the most frequent variant of futurity followed by the simple present (SP) and the morphological future (MF). Our findings reveal that, despite over two decades of communicative language teaching, Spanish FL textbooks still do not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Thus, the HLLs were likely exposed to all three verb forms in their childhood before they were explained in their Spanish classes. The L2 learners, on the other hand, were first exposed through textbooks and grammar explanations in the classroom setting, with the different representations of these forms, as compared to monolingual NS norms 2 , detailed in Orozco and Thoms (2014).…”
Section: Methods 41 Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the HLLs were likely exposed to all three verb forms in their childhood before they were explained in their Spanish classes. The L2 learners, on the other hand, were first exposed through textbooks and grammar explanations in the classroom setting, with the different representations of these forms, as compared to monolingual NS norms 2 , detailed in Orozco and Thoms (2014).…”
Section: Methods 41 Participantsmentioning
confidence: 99%
“…The most common variants used to express futurity are: (1) the periphrastic future (PF), (2) the morphological future (MF), and (3) the present indicative (PI). With a frequency of 70.8% across the Spanish-speaking world, the PF is considered the default marker of futurity, followed by the PI with 17.8% and the MF with 11.4% (Orozco and Thoms 2014).…”
Section: Future-time Expression In Monolingual Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research analyzing foreign language textbooks is growing and is quite diverse. Looking across the languages, some studies on Spanish textbooks examined the presentation of the future tense (Orozco & Thoms 2014) and articulatory phonetics (Arteaga 2000). A study on the typology of grammar activities in Italian textbooks conducted by Aski (2003) found that they still heavily rely on mechanical drills and are not reflective of the findings in research in second language acquisition.…”
Section: College-level Foreign Language Textbooksmentioning
confidence: 99%
“…En efecto, los aprendientes terminan por considerar el rasgo de relevancia actual como el rasgo defi nitorio de la perífrasis ir a + infi nitivo. Orozco y Thoms (2014), quienes analizan veinte libros de texto utilizados en el español L2 en universidades norteamericanas, afi rman que estos materiales favorecen la forma morfológica frente a la perífrasis para expresar la temporalidad futura, de manera contraria a los datos arrojados por los diversos estudios sociolingüísticos entre los hablantes nativos del español. Gozalo (2009:6) agrega, además, que los manuales y otros materiales pedagógicos usados en el español L2 "ofrecen ninguna o pocas soluciones satisfactorias para explicar la alternancia entre las formas de futuro" y que sería importante insistir en el hecho de que el uso de uno u otro recurso conlleva una diferencia importante de signifi cado.…”
Section: 2unclassified